IN VIVO STUDY OF PHENOLIC COMPOUNDS ROLE ON ANTIHYPERCHOLESTEROL ACTIVITY OF VIRGIN COCONUT OIL - Tri Joko Raharjo; Ariyani Setyo Widhiyati; Endah Mulya Asih; Sumiaty Sumiaty; Raden Tambunan; Ani Setyopratiwi (Universitas Gadjah Mada, 2008)
The role of phenolic compounds on antihypercholeserol activity of Virgin Coconut Oil (VCO) has been investigated. The in vivo studies ware carried out by treatment of two groups of Wistar white mouse (Ratus norvegicus) using high phenolic VCO and low phenolic VCO respectively, followed by analysis of lipid profile in blood and liver serum of the mouse. In addition a group of hypercholesterol mouse was treated with low phenolic VCO and the blood serum lipid profile was compared with untreated hypercholesterol mouse. The results show that phenolic compound play an important role on antihypercholesterol of VCO. Group of mouse treated with high phenolic VCO have better lipid profile (blood serum: total cholesterol: 70 mg/dL, triglyceride: 76 mg/dL, HDL: 20 mg/dL, LDL: 35 mg/dL; liver serum: total cholesterol:7 mg/dL, triglyceride: 19 mg/dL) compared with the group treated with low phenolic VCO (blood serum: total cholesterol: 82 mg/dL, triglyceride: 100 mg/dL, HDL: 21 mg/dL, LDL: 41 mg/dL; liver serum: total cholesterol: 9 mg/dL, triglyceride: 34 mg/dL). Hypercholesterol mouse tests shown that low phenolic VCO treatment result in decreasing of blood serum cholesterol level by 52.10% which was not significantly different compared to untreated mouses (decreasing of blood serum cholesterol level by 48.61%).